Dialysis outcomes in Colombia (DOC) study: A comparison of patient survival on peritoneal dialysis vs hemodialysis in Colombia (2008)
The goal of the Dialysis Outcomes in Colombia (DOC) study was to compare the survival of patients on hemodialysis (HD) vs peritoneal dialysis (PD) in a network of renal units in Colombia. The DOC study examined a historical cohort of incident patients starting dialysis therapy between 1 January 2001 and 1 December 2003 and followed until 1 December 2005, measuring demographic, socioeconomic, and clinical variables. Only patients older than 18 years were included. As-treated and intention-to-treat statistical analyses were performed using the Kaplan-Meier method and Cox proportional hazard model. There were 1094 eligible patients in total and 923 were actually enrolled: 47.3% started HD therapy and 52.7% started PD therapy. Of the patients studied, 751 (81.3%) remained in their initial therapy until the end of the follow-up period, death, or censorship. Age, sex, weight, height, body mass index, creatinine, calcium, and Subjective Global Assessment (SGA) variables did not show statistically significant differences between the two treatment groups. Diabetes, socioeconomic level, educational level, phosphorus, Charlson Co-morbidity Index, and cardiovascular history did show a difference, and were less favorable for patients on PD. Residual renal function was greater for PD patients. Also, there were differences in the median survival time between groups: 27.2 months for PD vs 23.1 months for HD (P less than 0.001) by the intention-to-treat approach; and 24.5 months for PD vs 16.7 months for HD (P less than 0.001) by the as-treated approach. When performing univariate Cox analyses using the intention-to-treat approach, associations were with age ?65 years (hazard ratio (HR)=2.21; confidence interval (CI) 95% (1.77-2.755); P less than 0.001); history of cardiovascular disease (HR=1.96; CI 95% (1.58-2.90); P less than 0.001); diabetes (HR=2.34; CI 95% (1.88-2.90); P less than 0.001); and SGA (mild or moderate-severe malnutrition) (HR=1.47; CI 95% (1.17-1.79); P=0.001); but no association was found with gender (HR=1.03, CI 95% 0.83-1.27; P=0.786). Similar results were found with the as-treated approach, with additional associations found with Charlson Index (0-2) (HR=0.29; Cl 95% (0.22-0.38); P less than 0.001); Charlson Index (3-4) (HR=0.61; Cl 95% (0.48-0.79); P less than 0.001); and SGA (mild-severe malnutrition) (HR=1.43; Cl 95% (1.15-1.77); P less than 0.001). Similarly, the multivariate Cox model was run with the variables that had shown association in previous analyses, and it was found that the variables explaining the survival of patients with end-stage renal disease in our study were age, SGA, Charlson Comorbidity Index 5 and above, diabetes, healthcare regimes I and II, and socioeconomic level 2. The results of Cox proportional risk model in both the as-treated and intention-to-treat analyses showed that there were no statistically significant differences in survival of PD and HD patients: intention-to-treat HD/PD (HR 1.127; CI 95%: 0.855-1.484) and as-treated HD/PD (HR 1.231; CI 95%: 0.976-1.553). In this historical cohort of incident patients, there was a trend, although not statistically significant, for a higher (12.7%) adjusted mortality risk associated with HD when compared to PD, even though the PD patients were poorer, were more likely to be diabetic, and had higher co-morbidity scores than the HD patients. The variables that most influenced survival were age, diabetes, comorbidity, healthcare regime, socioeconomic level, nutrition, and education. © 2008 International Society of Nephrology.